2016
DOI: 10.3945/ajcn.115.120147
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and caffeine consumption and the risk of hypertension in postmenopausal women

Abstract: In summary, these findings suggest that caffeinated coffee, decaffeinated coffee, and caffeine are not risk factors for hypertension in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 29 publications
2
41
2
2
Order By: Relevance
“…This study results showed significantly higher percentages of participants having less than 6 hours of sleep per night in the prehypertension group, consistent with reports suggesting that short sleep duration leads to an increase in systolic BP (Gangwisch, ). Contrary to previous studies, there was no difference in caffeine intake, HDL cholesterol levels, or sodium intake between the male prehypertension and normal BP groups in this study (Guo et al, ; Rhee et al, ; Shah et al, ). This result regarding caffeine can be attributed to the fact that 72% of the caffeine intake among Korean adults is from instant coffee mix, which is lower than that of brewed coffee (Korea Ministry of Food and Drug Safety, ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This study results showed significantly higher percentages of participants having less than 6 hours of sleep per night in the prehypertension group, consistent with reports suggesting that short sleep duration leads to an increase in systolic BP (Gangwisch, ). Contrary to previous studies, there was no difference in caffeine intake, HDL cholesterol levels, or sodium intake between the male prehypertension and normal BP groups in this study (Guo et al, ; Rhee et al, ; Shah et al, ). This result regarding caffeine can be attributed to the fact that 72% of the caffeine intake among Korean adults is from instant coffee mix, which is lower than that of brewed coffee (Korea Ministry of Food and Drug Safety, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to previous studies, there was no difference in caffeine intake, HDL cholesterol levels, or sodium intake between the male prehypertension and normal BP groups in this study (Guo et al, 2011;Rhee et al, 2016;Shah et al, 2016). This result regarding caffeine can be attributed to the fact that 72% of the caffeine intake among Korean adults is from instant coffee mix, which is lower than that of brewed coffee (Korea Ministry of Food and Drug Safety, 2015).…”
Section: Male Prehypertension Groupcontrasting
confidence: 93%
See 2 more Smart Citations
“…), does not increase hypertension (Rhee et al . ) nor cancer risk (Arab ) and may be protective against cardiovascular disease (Crippa et al . ).…”
Section: Human Intervention Studies On Hydroxycinnamic Acids and Coffeementioning
confidence: 99%